Intercultural Competence Acquisition of International Students Educators in Two Universities in Bulgaria and China - Juliana Popova (Journal of Danubian Studies and Research, 2017)
This paper argues on the importance of intercultural competence development of the academic and other staff, providing services to international students as part of the internalization policy of higher education. For this purpose two educational institutions are surveyed: Ruse University (RU), Bulgaria and Hubei University of Technology (HBUT), China. Recently, both universities have increased the number of their study abroad programs for local students, university programs for international students and exchange mobility transfers as part of their policies for internationalization. These institutions of higher education have also cooperated under the Erasmus+ program, which provided the authors with the possibility to elaborate a survey on the topic. Thus total of 29 international student educators participated in the study, which involved survey questionnaires in English, based on the Integrated Process Model of Intercultural Competence. The research results reveal that intercultural competence development is not a policy built-in practice or an organized process in these universities, which brings every-day challenges for the educators. Also, the findings confirm Hofstede‘s conclusion on organizational culture by showing that in spite of the differences between Bulgarian and Chinese national cultures, these two universities‘ policies, values and practices are very similar.